2021
DOI: 10.21203/rs.3.rs-585478/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production of High Amylose and Resistant Starch Rice Through Targeted Mutagenesis of Starch Branching Enzyme Iib by Crispr/cas9

Abstract: Rice is the staple food for half of the world’s population. Starch accounts for 80-90% of the total mass of rice seeds, and rice starch is low in resistant starch (RS) with a high glycemic index (GI). RS has gained important since it is beneficial in preventing various diseases. Starch branching enzyme IIb (SBEIIb) plays a key role in the amylopectin synthesis pathway in the endosperm of cereals. Down-regulation of SBEIIb in several important crops has led to high amylose, high RS and low GI starch. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Previous research on the indica rice cultivar (TNGS14) observed that AC increased dramatically from 15.8 % in wild type to 24.1% in the heterozygous condition and 30.8 % in the homozygous mutant lines [36]. Baysal et al [37] developed and analyzed T3 seeds from a homozygous mutant (E15 CRISPR/Cas9 edited line) with a 4 bp deletion, observed a 1.4 fold increase in amylose content in the edited line (27.4 %) compared to the wild type japonica cultivar Nipponbare (19.6 %).…”
Section: Resultsmentioning
confidence: 92%
“…Previous research on the indica rice cultivar (TNGS14) observed that AC increased dramatically from 15.8 % in wild type to 24.1% in the heterozygous condition and 30.8 % in the homozygous mutant lines [36]. Baysal et al [37] developed and analyzed T3 seeds from a homozygous mutant (E15 CRISPR/Cas9 edited line) with a 4 bp deletion, observed a 1.4 fold increase in amylose content in the edited line (27.4 %) compared to the wild type japonica cultivar Nipponbare (19.6 %).…”
Section: Resultsmentioning
confidence: 92%
“…The rice starch is low in resistant starch and has a high glycemic index. In the Japonica rice (cultivar TNG82), the CRISPR-Cas9 editing of the OsSBEIIb gene resulted in increased resistant starch production and decreased reducing sugar production, as a result, the glycemic index in homozygous and heterozygous CRISPR-Cas mutant rice endosperms was reduced by 28% and 11%, respectively [122] .…”
Section: Crispr For the Crop Improvement And Agricultural Biotechnologymentioning
confidence: 99%
“…In Limosilactobacillus reuteri a two-step approach using ssDNA and the CRISPR-Cas system was used for targeted codon mutagenesis, improving the number of recoverable recombinants, as well as identification of recombinant cells in bacteria with low recombineering efficiencies. This technology allowed the selection of oligonucleotide-mediated chromosomal deletions up to 1 kb, and it excluded the need for ssDNA recombineering optimization procedures [122] .…”
Section: Crispr-cas Systems Applied In Food Industrymentioning
confidence: 99%